Pengaruh Pemanfaatan Teknologi Informasi, Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan - Febrianita Hadis; Hidayatul Ihsan; Anda Dwiharyadi; Yossi Septriani; Zalida Afni (Jurusan Akuntansi Politeknik Negeri Padang, 2022)
This study aims to determine the effect of the use of information technology and the competence of financial management human resources on the quality of financial reports. The samples in this study were treasurers and financial management staff at Andalas University, Padang City. Data collection in this study used the questionnaire method consisting of 29 questions based on the indicators of each variable which were distributed directly to treasurers and financial management staff of 68 people and 68 people returning questionnaires. Testing the research data using multiple linear regression analysis with statistical testing of the hypothesis test Coefficient of Determination (R²), Simultaneous (F Test) and Statistical Test t, type of descriptive research. With the research results, the use of information technology has a positive effect on the quality of financial reports at Andalas University in Padang City. This can prove that when information technology facilities are properly installed, optimal utilization, scheduled maintenance can improve the quality of financial reports. Competence of Human Resources for financial managers has a positive effect on the quality of financial reports at Universities in Padang City. This can prove that when financial management human resources have the knowledge, skills and attitudes that support them in carrying out their functions, they can improve the quality of financial reports.